Could banning virtual assets be a breach of the doctrine of legitimate expectation? - Moniruzzaman, Md.; Haq, Md. Zahurul; Farzana, Kazi Fahmida (Emerald Publishing Limited, 2021)
Despite its wide acceptance as a digital representation of value (Hanafi and Rahman, 2019, pp. 271–278), cryptocurrency’s legal status remains doubtful in many jurisdictions. Even more perplexing is the regulators’ implicit ban, which does not often explain what elements of illegality are involved in owning and transferring this value. One of such jurisdictions is Bangladesh, where the legal status of cryptocurrency is unresolved even under growing threats of its abuse. On the one hand, Bangladesh Bank – the central bank of Bangladesh –has imposed an implicit ban on cryptocurrencies because of their alleged criminal nature (Bangladesh Bank, 2014, 2017). Their position has not changed since then. On the other hand, the Information and Communication Technology Division (ICTD) of the government indicated they were willing to support research and innovation in cryptocurrencies (ICTD,2020, pp. 41–46). This simultaneous awareness of opposing views of two important public agencies on a crucial policy issue indicates that the amount of confusion among policymakers on cryptocurrency is high.